Investigating the Gap between Planned and Implemented Neighborhood Layout Plans of Minor Towns: A Case of Mlowo Township in Songwe, Tanzania - Mchome, Emmanuel Elifadhili; Nzoya, Uwezo Wilbard (Recent Research Advances in Arts and Social Studies Vol. 6, 2024)
The aim of this study was to investigate the possible reasons and challenges in implementing the NLP‘s in minor towns. Minor towns have specific roles in the economic development due to fact that they possess intermediate position between big cities and rural settlements. For centuries, minor towns have played a great intermediate role between rural areas and urban areas in the world. Many worldwide literatures reveal that the settlements contribute much in economic development of both urban and rural areas. Land development in these settlements is guided by detailed layout plans including neighborhood layout plans (NLPs) and Regularization Schemes. In Tanzania, preparation of NLPs in these settlements is under Township Authorities and District Councils. However, the current trend shows that, most of the prepared NLPs in minor towns remain only on the office papers and contradict to what is developed on the ground. The situation has been contributed by unique planning challenges and approaches used in planning of these settlements. The study employed both primary and secondary data collection methods. The primary data methods were interview and survey while secondary data were obtained through published documents such as population and housing census reports. Thereafter, the data were analysed with the help of Statistical Package for Social Sciences (SPSS) and Microsoft excel. It comes out from the findings that most of the prepared NLPs in the townships experience incomplete implementation whereas the implementation goals are not attained. Most of the prepared NLPs in the townships experience incomplete implementation whereas the implementation goals are not attained. This is caused by having many plans whose preparation are influenced by only one or few clients who are financially stable and are able to finance the layout preparation process. Moreover, wrong interpretation and application of the legal frameworks guiding NLPs preparation and; lack of the implementation action plans constrain the planning process in the minor towns. The study recommends on; reforming legal systems guiding preparation and implementation of the NLPs; preparing the Implementation Action Plan to guide NLP’s implementation process and; economic stabilization of the township authorities.